Theoretical substantiation of the influence of parameters on the quality and energy performance of a slope-type plug-type softener - V.Ortikov, D.B.Irgashev (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Bentleg furrow openers can significantly reduce soil disturbance and reaction forces relative to conventional narrow point openers used in no-tillage farming. The effect of bentleg opener geometry on soil disturbance and reaction forces in a cohesive soil was assessed in a virtual soil bin using the discrete element method.Furrow size was found to be more dependent on shank lateral offset and side leg bend angle than side leg forward angle. Though side leg forward angles >90° reduce particle displacement and will work better in fields with stones and roots, they also considerably increase draught and penetration resistance. A low rake angled foot minimises soil reaction forces and drives soil loosening. Reducing foot height and interaction of the vertical shank with soil particles minimises surface soil displacement. These results have expanded the understanding of bentleg opener mechanics and are in close agreement with those reported for sandy soils. Therefore, similar criteria can be followed to optimise bentleg opener design for different soil types.